Determinación del nivel crítico del nemátodo helicotylenchus multicinctus en plantas de Banano (musa aaa) y plátano (musa aab), establecidas en invernadero y área comercial - Delgado Párraga, Alex (2013)
Determination of the economic threshold of nematode Helicotylenchus multicinctus in banana plants (Musa AAA) and plantain (Musa AAB), established in the greenhouse and commercial area in 2012 – 2013. Population densities of H. multicinctus were distributed in 19 treatments with 5 replicates (plants) that were grouped into low 1000 – 3000, average 3500 – 7000, high 8000 – 12000 populations and the control (0). We used completely randomized design and Duncan mean test at 5 %. In the trials of banana and plantain, in greenhouse, were used 190 plastic bags with solarized soil, 15 cm seedlings were transplanted, after a month, the treatments were inoculated. The irrigation was done according to the requirements of the plants. At 90 days were evaluated: In the group of 1000 – 3000, in banana and plantain root weight was statistically similar to the control and the 8000 – 12000 group, in banana there was an increase in the weight of functional roots, in the case of plantain, in this same group, the amount was reduced